2013
DOI: 10.1111/adb.12074
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nicotine self-administration and suppressed dopaminergic systems in a rat model of diabetes

Abstract: Patients with diabetes display a heightened propensity to use tobacco; however, it is unclear whether they experience enhanced rewarding effects of nicotine. Thus, this study examined the reinforcing effects of nicotine in a rodent model of diabetes involving administration of streptozotocin (STZ), a drug that is toxic to pancreatic insulin-producing cells. The first study compared STZ- and vehicle-treated rats that had 23-hour access to intravenous self-administration (IVSA) of nicotine or saline and concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 62 publications
9
46
0
Order By: Relevance
“…The STZ model generally represents the etiology of type 1 diabetes or advanced stages of type 2 diabetes (Bell Jr. and Hye, 1983). The STZ model has been extensively studied and used to assess the complications of type 1 diabetes (Badalzadeh et al, 2015;Piculo et al, 2014), learning and memory (Bellush and Rowland, 1989;Flood et al, 1990), natural hedonic processing and drug reward (Carr, 1994;Carr et al, 2000;Galici et al, 2003b;O'Dell et al, 2014). Thus, the STZ model represents a common method of inducing diabetes via disruptions in insulin signaling.…”
Section: Rodent Models Of Diabetes Used To Study Nicotine Rewardmentioning
confidence: 99%
See 2 more Smart Citations
“…The STZ model generally represents the etiology of type 1 diabetes or advanced stages of type 2 diabetes (Bell Jr. and Hye, 1983). The STZ model has been extensively studied and used to assess the complications of type 1 diabetes (Badalzadeh et al, 2015;Piculo et al, 2014), learning and memory (Bellush and Rowland, 1989;Flood et al, 1990), natural hedonic processing and drug reward (Carr, 1994;Carr et al, 2000;Galici et al, 2003b;O'Dell et al, 2014). Thus, the STZ model represents a common method of inducing diabetes via disruptions in insulin signaling.…”
Section: Rodent Models Of Diabetes Used To Study Nicotine Rewardmentioning
confidence: 99%
“…To study nicotine reward, a model involving 23-hour access to intravenous self-administration of nicotine was used (O'Dell et al, 2014). The latter study also compared nicotine metabolism and dose-dependent effects of nicotine self-administration across groups.…”
Section: Enhanced Nicotine Reward In Rodent Models Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that STZtreated rats display a profound suppression of dopamine release and D1 receptors in the NAcc [62]. Also, STZ-treated rats display a suppression of dopamine release in the dorsal striatum [90][91][92][93][94].…”
Section: Mechanisms Of Nicotine Withdrawal In Vulnerable Populationsmentioning
confidence: 91%
“…The HFD model of diabetes produces insulin resistance and hyperglycemia following chronic exposure to a HFD regimen. Pre-clinical studies have revealed that STZ-treated rats display higher levels of nicotine IVSA as compared to healthy controls [62]. A subsequent study revealed that insulin resistance, produced by HFD regimen, potentiates CPP produced by nicotine [63].…”
Section: Tobacco Use In Vulnerable Populationsmentioning
confidence: 99%